Association of EGFR mutation or ALK rearrangement with expression of DNA repair and synthesis genes in never-smoker women with pulmonary adenocarcinoma - Ren, Shengxiang; Schmid-Bindert, Gerald (Cancer, 2012)
BACKGROUND: Epidermal growth factor receptor (EGFR) mutation and anaplastic lymphoma kinase (ALK) rearrangement may predict the outcome of targeted drug therapy and also are associated with the efficacy of chemotherapy in patients with nonsmall cell lung cancer (NSCLC). The authors of this report investigated the relation of EGFR mutation or ALK rearrangement status and the expression of DNA repair or synthesis genes, including excision repair cross-complementing 1 (ERCC1), ribonucleotide reductase subunit M1 (RRM1), thymidylate synthetase (TS), and breast cancer-early onset (BRCA1), as a potential explanation for these observations. METHODS: In total, 104 resected lung adenocarcinomas from women who were nonsmokers were analyzed concurrently for EGFR mutations, ALK rearrangements, and mRNA expression of the ERCC1, RRM1, TS, and BRCA1 genes. EGFR mutations were detected with a proprietary detection kit, ALK rearrangements were detected by polymerase chain reaction analysis, and genetic mRNA expression was detected by real-time polymerase chain reaction analysis. RESULTS: Of 104 patients, 73 (70.2%) had EGFR mutations, and 10 (9.6%) had ALK rearrangements. ERCC1 mRNA levels in patients who had EGFR mutations were 3.44 ± 1.94 × 10−3, which were significantly lower than the levels in patients who were positive for ALK rearrangements and in patients who were negative for both biomarkers (4.60 ± 1.95 × 10−3 and 4.95 ± 2.33 × 10−3, respectively; P = .010). However, TS mRNA levels were significantly lower in patients who had EGFR mutations (1.15 ± 1.38 × 10−3 vs 2.69 ± 3.97 × 10−3; P = .006) or ALK rearrangements (1.21 ± 0.78 × 10−3 vs 2.69 ± 3.97 × 10−3; P = .020) than in patients who were negative for both biomarkers. CONCLUSIONS: NSCLC specimens that harbored activating EGFR mutations were more likely to express low ERCC1 and TS mRNA levels, whereas patients with NSCLC who had ALK rearrangement were more likely to express low TS mRNA levels. Cancer 2012. © 2012 American Cancer Society.
Gesehen am 16.05.2018